A new species of Paralaophonte Lang 1948 (Harpacticoida: Laophontidae), with notes on the phylogeny of the genus and its relationships with Loureirophonte Jakobi 1953 using Bayesian inference - Gómez, Samuel; Nazari, Fatemeh (Zootaxa, 2021)
Early studies during the 1990’s supported a close relationship between the genera Paralaophonte and Loureirophonte. Subsequent studies carried out during the first decade of the 2000’s suggested the monophyly of the latter and that it could be nested within Paralaophonte, rendering the latter paraphyletic. However, efforts to synonymize these two genera were hampered by the lack of phylogenetic analyses at the species level. Here we describe a new species of Paralaophonte from north-western Mexico, P. ullama sp. nov., and we formally synonymize Loureirophonte with Paralaophonte for which we propose two monophyletic subgenera, Pa. (Paralaophonte) and Pa. (Loureirophonte). The detection of the species most closely related to P. ullama sp. nov. is controversial. Our Bayesian analysis indicates that the new species might be related to Pa. (Pa.) gurneyi, and to Pa. (Pa.) ormieresi and Pa. (Pa.) septemarticulata, with which they form a larger clade supported by a very low Bayesian Posterior Probability value. However, the precise nature of the relationship between the new species and Pa. (Pa.) gurneyi is hampered by the gap in our knowledge of the armature formulae of the swimming legs of the latter, and by the lack of the male of the new species. On the other hand, the new species share several characters with Pa. (Pa.) problematica, Pa. (Pa.) pacificavicinum, Pa. (Pa.) pacificaemulator, and Pa. (Pa.) pacifica, with which it might be related. Our Bayesian analysis of forty-two morphological characters at the species level confirmed earlier suspicions about the relationships between Paralaophonte and Loureirophonte, the latter being nested within the former, and showed the monophyly of the Paralaophonte-Loureirophonte clade with high Bayesian Posterior Probability value, thus confirming the synonymy of these genera. The Paralaophonte-Loureirophonte clade is defined by the synapomorphic dimorphism in the second endopodal segment of the second swimming leg of the male. We did not detect any (aut)apomorphy for Pa. (Paralaophonte). Paralaophonte (Loureirophonte) is defined by the presence of one seta only on the second endopodal segment of the second swimming leg, and the one-segmented endopod of the fourth swimming leg.